Two types of flexibility: in coping and cognitive, and their relationship with stress among firefighters - Agata Borzyszkowska; Małgorzata Anna Basińska (Nofer Institute of Occupational Medicine, 2020)
Background Flexibility in coping with stress and cognitive flexibility are new constructs both in Polish and European psychological sciences. A person displaying flexibility in coping has a wide repertoire of remedial strategies, which he or she is able to change if the situation so requires, and which reflect on the strategies used, while a person displaying cognitive flexibility is ready to look for new ways to cope. The profession of a firefighter involves exposure to various stressors, and occupational stress can affect not only mental health, but also the quality of work performed. That is why flexibility in coping with stress and cognitive flexibility seem so important. The aim of the study was to perform empirical verification of the relationship between flexibility in coping and cognitive flexibility, as well as to determine their relationship with the stress perceived by the respondents. Material and Methods Overall, 104 firefighters (males only) were qualified for the examination. The average age of the respondents was 34 years (SD = 7.81). The Flexibility in Coping with Stress Questionnaire (FCSQ-14), the Cognitive Flexibility Inventory (CFI) and the Perceived Stress Scale (PSS-10) were used. Results There is a statistically significant relationship between flexibility in coping with stress and its dimensions, and cognitive flexibility and its dimensions, in the examined group of firefighters. The strongest positive relationship was observed between cognitive flexibility and repertoire (r = 0.639, p < 0.001), and the weakest between cognitive control and reflectivity (r = 0.257, p = 0.009). A statistically significant negative relationship was found between flexibility in coping with stress (r = -0.339, p = 0.001) and cognitive flexibility (r = -0.359, p < 0.001), and stress experienced by the respondents. There was no statistically significant relationship between reflectivity, which is a dimension of flexibility in coping with stress, and perceived stress. Conclusions There is a need to consider the possibility of including in the prevention programs addressed to firefighters the need to support subjective resources, which include flexibility in coping with stress and cognitive flexibility. The results also indicate the need to deepen research in order to better understand the constructs of flexibility in coping with stress and cognitive flexibility. Med Pr. 2020;71(4):441-50